«The First Inuit Novel Written: A Significant Literary and Social Achievement. Abridged introduction. Markoosie, Harpoon of the Hunter» - Chartier, Daniel (Presses de l'Université du Québec, 2011)
Abbreviated introduction to the new publication in French and Inuktitut of the first Inuit novel in Canada, Markoosie, Harpoon of the Hunter. The author addresses issues of Inuit literature, the influence of the Other within this literature, the reception and the historical significance of the novel, the life of its author Markoosie Patsauq, the narrative construction of the work , themes such as survival, solidarity, violence, suicide and, finally, the symbolism of the spear.